Serum Irisin level in patients undergoing different Stages of Chronic Kidney Disease - Javad Sadeghishad; Roghayeh Akbari; Durdi Qujeq; karimollah Hajian (Babol University of Medical Sciences, 2019)
Background: Irisin is a myokine that regulates energy metabolism by inducing browning of adipose tissue. The aim of this study was to evaluate the relationship between irisin level and biochemical parameters of chronic kidney disease (CKD) patients in stage 2 and stage 4. Methods: The research was a cross-sectional study; the study population included patients with CKD who were over 18 years of age, included 90 individuals with CKD, of these participants, 45 were in the second stage of the CKD while the other 45 subjects were in the fourth stage. Serum irisin concentration plus the level of glucose (Glu), urea, creatinine (Cr) and hemoglobin (Hb) were measured. Results: In the present study, the serum irisin level of patients in stage 4 was significantly reduced (13.00 ng / ml) compared with patients in stage 2(21.41 ng / ml). Conclusion: With the progression of CKD from stage 2 to stage 4, parameters such as serum Cr, TG, LDL, FBS, BUN and urea levels significantly increased. Inversely, factors such as irisin, GFR, Alb, HDL and Hb levels significantly decreased. These findings suggest that irisin may be involved in the regulation of biochemical factor levels in CKD patients through the progression from stage 2 to stage 4.